Safety and immunogenicity of rSh28GST antigen in humans: phase 1 randomized clinical study of a vaccine candidate against urinary schistosomiasis. - Gilles Riveau; Dominique Deplanque; Franck Remoué; Anne-Marie Schacht; Hubert Vodougnon; Monique Capron; Michel Thiry; Joseph Martial; Christian Libersa; André Capron (Public Library of Science (PLoS), 2012)
Treatment of urinary schistosomiasis by chemotherapy remains challenging due to rapid re-infection and possibly to limited susceptibility to praziquantel treatment. Therefore, therapeutic vaccines represent an attractive alternative control strategy. The objectives of this study were to assess the safety and tolerability profile of the recombinant 28 kDa glutathione S-transferase of Schistosoma haematobium (rSh28GST) in healthy volunteers, and to determine its immunogenicity.Volunteers randomly received 100 µg rSh28GST together with aluminium hydroxide (Alum) as adjuvant (n = 8), or Alum alone as a comparator (n = 8), twice with a 28-day interval between doses. A third dose of rSh28GST or Alum alone was administered to this group at day 150. In view of the results obtained, another group of healthy volunteers (n = 8) received two doses of 300 µg of rSh28GST, again with a 28-day interval. A six-month follow-up was performed with both clinical and biological evaluations. Immunogenicity of the vaccine candidate was evaluated in terms of specific antibody production, the capacity of sera to inhibit enzymatic activity of the antigen, and in vitro cytokine production.Among the 24 healthy male participants no serious adverse events were reported in the days or weeks after administration. Four subjects under rSh28GST reported mild reactions at the injection site while a clinically insignificant increase in bilirubin was observed in 8/24 subjects. No hematological nor biochemical evidence of toxicity was detected. Immunological analysis showed that rSh28GST was immunogenic. The induced Th2-type response was characterized by antibodies capable of inhibiting the enzymatic activity of rSh28GST.rSh28GST in Alum did not induce any significant toxicity in healthy adults and generated a Th2-type immune response. Together with previous preclinical results, the data of safety, tolerability and quality of the specific immune response provide evidence that clinical trials with rSh28GST could be continued in humans as a potential vaccine candidate against urinary schistosomiasis.